SERVICE QUALITY IN THE PUBLIC SERVICE OF LATVIA - Katelo, Iveta; Kokina, Irēna; Raščevskis, Vitālijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Improvement of quality of public services is one of the important goals in the advancement of the operation of state / public administration in Latvia. The aim of the research was to evaluate the quality of customer service in the institutions of public administration in Latvia, to perform the factor analysis of the collected data.The research was based on the selection of customers of public services, in total of 292 people in Riga and in Latvian regional centres in 2017-2018. The research was conducted in public institutions of Latvian regions that provide social assistance (SSIA – the State Social Insurance Agency), offer employment promotion services (SEA – the State Employment Agency); realize tax policy in the state (SRS – the State Revenue Service), implement the state environmental protection policy (MEPRD – Ministry of Environment Protection and Regional Development); provide legal aid services (DC – Daugavpils Court). The quality of services provided to the clients of corresponding institutions was evaluated. For the data collection, the service quality assessment model – the SERVQUAL instrument (Parasuraman et al., 1988) was used, as well as the analysis of the research data factors was carried out.The service quality assessment revealed that the performance of public service organizations in Latvia does not meet the customers’ expectations. The evaluation of service quality provided by public authorities, as well as their regular monitoring would improve the quality of services provided.